Helping Hand or Competition? The Moderating Influence of Perceived Upward Mobility on the Relationship Between Blended Workgroups and Employee Attitudes and Behaviors - George, Elizabeth; Chattopadhyay, Prithviraj; Zhang, Lida L. (Organization Science, 2012)
This study attempts to reconcile previous findings that show both positive and negative outcomes associated with blended workgroups (i.e., workgroups consisting of both temporary and standard workers). Specifically, we conceptualize temporary and standard work as part of a naturally occurring status hierarchy in organizations and propose that blended workgroups have opposing effects on employees depending on employees' perceptions of their potential for upward mobility in that organization. We combine research on the blended workforce with theorizing from social identity and self-categorization theories to propose that when employees perceive the potential for upward mobility to be high, the proportion of temporary workers in the group will be negatively related to employee attitudes and behaviors, and the relationship will be positive when perceived mobility is low. Furthermore, we hypothesize that this relationship will be mediated by the valence of employees' perceptions of their workgroup's prototype. We test our hypotheses on a sample of 124 temporary and standard research scientists in an Australian organization. The results show that workgroup composition and perceived mobility jointly influence workgroup identification and organization-based self-esteem, mediated by the valence of workgroup prototype; however, workgroup composition and perceived mobility directly influence organizational citizenship behavior unmediated by prototype valence.